1994
DOI: 10.1164/ajrccm.150.3.8087337
|View full text |Cite
|
Sign up to set email alerts
|

Ozone dose and effect in humans and rats. A comparison using oxygen-18 labeling and bronchoalveolar lavage.

Abstract: In an effort to improve risk assessments for ozone (O3) we compared the incorporation of inhaled oxygen-18-labeled O3 (18O3) into the lungs of humans and laboratory rats. Cells and fluids obtainable through bronchoalveolar lavage (BAL) were examined after exposure to 18O3 to determine whether excess 18O concentrations (presumed to be reaction products of 18O3) could be detected and equated to the O3 dose to the lung. Three O3 effect measurements (increased BAL protein and neutrophils and decreased BAL macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
152
2
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(159 citation statements)
references
References 25 publications
0
152
2
2
Order By: Relevance
“…Mice were exposed continuously (for 6, 24, or 48 h) to 0.3 ppm O 3 . On the basis of National Ambient Air Quality Standards for ambient O 3 (0.12 ppm for 1 h and 0.08 ppm for 8 h) (26) and dosimetry studies in which rodents require four-to fivefold higher doses of O 3 than humans to create an equal deposition and pulmonary inflammatory response (27), the O 3 concentration used in the current study is a reasonable exposure level from which to make comparisons with humans. O 3 was generated from ultra-high-purity air (Ͻ 1 ppm total hydrocarbons; National Welders, Inc., Raleigh, NC) using a silent arc discharge O 3 generator (model L-11; Pacific Ozone Technology, Benicia, CA).…”
Section: Animals and Inhalation Exposurementioning
confidence: 99%
“…Mice were exposed continuously (for 6, 24, or 48 h) to 0.3 ppm O 3 . On the basis of National Ambient Air Quality Standards for ambient O 3 (0.12 ppm for 1 h and 0.08 ppm for 8 h) (26) and dosimetry studies in which rodents require four-to fivefold higher doses of O 3 than humans to create an equal deposition and pulmonary inflammatory response (27), the O 3 concentration used in the current study is a reasonable exposure level from which to make comparisons with humans. O 3 was generated from ultra-high-purity air (Ͻ 1 ppm total hydrocarbons; National Welders, Inc., Raleigh, NC) using a silent arc discharge O 3 generator (model L-11; Pacific Ozone Technology, Benicia, CA).…”
Section: Animals and Inhalation Exposurementioning
confidence: 99%
“…Ozone concentrations of 1ppm were used to enhance allergic responses in a rat strain that is comparatively less sensitive to ozone than other rats or humans. Pulmonary ozone dosimetry studies demonstrate that humans have 4-5 times greater pulmonary deposition of inhaled ozone than Fisher F344 rats [30], and that rats required greater exposures for similar responses. Furthermore the Brown Norway rat is much less sensitive to ozone than F344 rats.…”
Section: Ozone Exposurementioning
confidence: 99%
“…Components of air pollution such as ozone and endotoxin are well-documented to exacerbate the symptoms of asthma, and may also play a role in the initiation of this disease. Although our study used a high concentration of ozone, exposure to 2 ppm of ozone in a rodent was shown to be comparable to 0.2 ppm of ozone in a susceptible human subject (30). Ozone and LPS pre-exposures have been shown to alter the innate immune response to pathogens in mice, as well as in murine and human macrophages.…”
Section: Discussionmentioning
confidence: 72%